Nano aerosols in the Postojnska jama - Iskra, Ivan; Kávási, Norbert; Vaupotič, Janja (Acta Carsologica, 2010)
At the lowest point in the Postojnska Jama (jama = cave), concentration and size distribution of non-radioactive aerosols in the size range of 10–1,000 nm were measured and their concentrations are compared with those of radioactive aerosols carrying radon short-lived decay products (218Po, 214Pb and 214Bi) obtained previously. Concentration of non-radioactive aerosols during morning hours was in the range 600–2,750 cm–3, with about 90% of particles smaller than 50 nm. On the other hand, concentration of radioactive aerosols smaller than 50 nm was several radionuclide atoms per 1 cm3 and the bigger ones, less than 1 atom per 1 cm3.